"I don't eat a hamburger and large chips every day!" A qualitative study of the impact of public health messages about obesity on obese adults - Blood R Warwick; Castle David; Hyde Jim; Thomas Samantha L; Lewis Sophie; Komesaroff Paul A (BMC, 2010)
Abstract Background We are a society that is fixated on the health consequences of 'being fat'. Public health agencies play an important role in 'alerting' people about the risks that obesity poses both to individuals and to the broader society. Quantitative studies suggest people comprehend the physical health risks involved but underestimate their own risk because they do not recognise that they are obese. Methods This qualitative study seeks to expand on existing research by exploring obese individuals' perceptions of public health messages about risk, how they apply these messages to themselves and how their personal and social contexts and experiences may influence these perceptions. The study uses in depth interviews with a community sample of 142 obese individuals. A constant comparative method was employed to analyse the data. Results Personal and contextual factors influenced the ways in which individuals interpreted and applied public health messages, including their own health and wellbeing and perceptions of stigma. Individuals felt that messages were overly focused on the physical rather than emotional health consequences of obesity. Many described feeling stigmatised and blamed by the simplicity of messages and the lack of realistic solutions. Participants described the need for messages that convey the risks associated with obesity while minimising possible stigmatisation of obese individuals. This included ensuring that messages recognise the complexity of obesity and focus on encouraging healthy behaviours for individuals of all sizes. Conclusion This study is the first step in exploring the ways in which we understand how public health messages about obesity resonate with obese individuals in Australia. However, much more research - both qualitative and quantitative - is needed to enhance understanding of the impact of obesity messages on individuals.